Efficacy of ginger as antiemetic in children with acute gastroenteritis: a randomised controlled trial. Issue 1 (21st May 2021) - Nocerino, Rita; Cecere, Gaetano; Micillo, Maria; De Marco, Giulio; Ferri, Pasqualina; Russo, Mariateresa; Bedogni, Giorgio; Berni Canani, Roberto
Summary: Background: Ginger is a spice with a long history of use as a traditional remedy for nausea and vomiting. No data on the efficacy of ginger are presently available for children with vomiting associated with acute gastroenteritis (AGE). Aim: To test whether ginger can reduce vomiting in children with AGE. Methods: Double‐blind, randomised placebo‐controlled trial in outpatients aged 1 to 10 years with AGE‐associated vomiting randomised to ginger or placebo. The primary outcome was the occurrence of ≥1 episode of vomiting after the first dose of treatment. Severity of vomiting and safety were also assessed. Results: Seventy‐five children were randomised to the ginger arm and 75 to the placebo arm. Five children in the ginger arm and 4 in the placebo arm refused to participate in the study shortly after randomisation, leaving 70 children in the ginger arm and 71 in the placebo arm (N = 141). At intention‐to‐treat analysis (N = 150), assuming that all children lost to follow‐up had reached the primary outcome, the incidence of the main outcome was 67% (95% CI 56 to 77) in the ginger group and 87% (95% CI 79 to 94) in the placebo group, corresponding to the absolute risk reduction for the ginger versus the placebo group of −20% (95% CI −33% to −7%, P  = 0.003), with a number needed to treat of 5 (95% CI 3 to 15). Conclusion: Oral administration of ginger is effective and safe at improving vomiting in children with AGE. Trial registration : The trial was registered on https://clinicaltrials.gov/ with the identifier NCT02701491. Abstract : In a double‐blind, randomised placebo‐controlled trial in pediatric outpatients with acute gastroenteritis (AGE)‐associated vomiting the oral administration of ginger resulted effective and safe at improving vomiting.